Synthesis of Dibenzo[f,h]quinolines by Stepwise C–H Arylation of 2-Phenylpyridine and Reductive Cyclodehydrogenation - He, Yan-Qin; Li, Zhong-Qiu; Zhong, Yu-Wu (Synthesis, 2023)
A synthetic approach to dibenzo[f,h]quinolines and their derivatives via stepwise ruthenium-catalyzed C–H arylation and potassium-mediated reductive cyclodehydrogenation from 2-phenylpyridine and aryl bromides, is presented. One dibenzo[f,h]quinoline derivative is used as a bidentate ligand to prepare a cyclometalated ruthenium complex. Two dibenzo[f,h]quinoline compounds and the ruthenium complex were characterized by single-crystal X-ray structural analysis.
Keywords: dibenzo[f,h]quinolones; polycyclic aromatic hydrocarbons; C–H arylation; reductive cyclodehydrogenation; ruthenium